2018
DOI: 10.3390/nu10060793
|View full text |Cite
|
Sign up to set email alerts
|

Inulin Supplementation Does Not Reduce Plasma Trimethylamine N-Oxide Concentrations in Individuals at Risk for Type 2 Diabetes

Abstract: Trimethylamine N-oxide (TMAO) is associated with type 2 diabetes (T2DM) and increased risk of adverse cardiovascular events. Prebiotic supplementation has been purported to reduce TMAO production, but whether prebiotics reduce fasting or postprandial TMAO levels is unclear. Sedentary, overweight/obese adults at risk for T2DM (n = 18) were randomized to consume a standardized diet (55% carbohydrate, 30% fat) with 10 g/day of either an inulin supplement or maltodextrin placebo for 6 weeks. Blood samples were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…The present study population was unique compared to other studies that examined Mediterranean dietary patterns and TMAO concentration in that the population was based in North America. Additionally, the subjects were at increased risk for colon cancer but were otherwise healthy 16,22,38 . The dietary intervention was not associated with reductions in serum TMAO concentration despite elevated fasting concentrations at baseline compared with another study from our group looking at younger adults with lower baseline TMAO concentration 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study population was unique compared to other studies that examined Mediterranean dietary patterns and TMAO concentration in that the population was based in North America. Additionally, the subjects were at increased risk for colon cancer but were otherwise healthy 16,22,38 . The dietary intervention was not associated with reductions in serum TMAO concentration despite elevated fasting concentrations at baseline compared with another study from our group looking at younger adults with lower baseline TMAO concentration 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Current research is underway to evaluate dietary strategies to reduce TMAO concentration by influencing TMA release by the gut microbiome 7,12,13 . However, previous studies from our group have shown that traditional approaches to modulating the composition and function of the microbiome (prebiotics and probiotics), as well as short-term flavonoid intervention 14 , failed to reduce circulating TMAO concentrations 15,16 . A choline analog (3,3,-dimethylbutanol) has emerged as an effective inhibitor of choline metabolism and subsequent TMAO production in rodents 8 , but this compound is currently not approved for human use.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recent evidence from animal studies suggest that soluble dietary fibre reduces TMA and TMAO metabolism by 40.6 and 62.6%, respectively, which was associated with increased SCFA production and reduced serum lipids and cholesterol [ 63 ]. In contrast, inulin supplementation in humans had no effect on fasting or post-prandial TMAO levels [ 64 ], indicating the challenges in translating findings from animals to humans and the complexity of the role of different dietary fibres on microbial activity.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of inulin [ 70 ], chromium [ 97 ], galacto-oligosaccharides [ 39 ] and betaine [ 73 ] supplementation were reported by one study each. None reported any significant positive metabolic effect nor decrement in diabetic risk factors.…”
Section: Resultsmentioning
confidence: 99%